School Bullying: Introducing the Issue - Rana, Niti (Journal of Education and Research, 2008)
Beginning of the world. Void reigned then. Darkness alone existed. ! en God created light. Soon he created land, rivers, hills and humans. But he was not satisfied with this multitude. He desperately wanted to carve the most beautiful creature on the earth. So at one fi ne heavenly moment, he set himself for the task. He then took all the lovely features from different creatures and lumped them into his new creation. "Abracadabra! Abracadabra!" chanted God, and lo! There emerged a camel. DOI: http://dx.doi.org/10.3126/jer.v1i0.7952 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 62-68